A Private Label Branding Strategies Towards Digital Marketing Of Amazon In Chennai City - K, Sindhuja; Fathima Rani, S. Vennila (Journal of Neonatal Surgery, 2025)
The study aims to investigate the impact of private label branding strategies on digital marketing with special reference to Amazon. A snow-ball sampling technique was used to collect data from 509 consumers of private label brands. A cause and effect research design was used, and a questionnaire was developed to collect data. The study found that promotion, credibility, and product recognition in the market have a significant impact on private label branding strategies in digital marketing. The results also revealed that branding strategies have a significant impact on digital marketing of Amazon. Additionally, development effort plays a partial mediation role between private label branding strategies and digital marketing success. Furthermore, the study found that academic qualification of consumers has a significant impact on credibility, product recognition, and development effort of Amazon towards private label branding. The findings provide valuable insights for companies like Amazon to develop effective private label branding strategies that can be integrated with digital marketing efforts to gain a competitive advantage in the market.